Analysis Of Internet Utilization In Learning Physical And Educational Culture For Students' Abilities At Smps Bina Agung Medan In The 2024/2025 Academic Year - Sitohang, Stephen Otniel; Isnandar, Muhammad (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to determine the level of internet utilization as a learning resource for Physical Education (PJOK) by students at Bina Agung Medan Junior High School. This study was conducted because the level of internet utilization as a learning resource was unknown.This is a descriptive qualitative study using a survey method. The instrument used was a questionnaire. Respondents in this study were 38 students from two classes at Bina Agung Medan Junior High School. The data analysis technique used was descriptive with percentages.The study showed that internet utilization in PJOK learning at Bina Agung Medan Junior High School was categorized as moderately influential with 14 statements (53.84%), moderately influential with 11 statements (42.30%), and very influential with 1 statement (3.84%). Therefore, from these results, it can be concluded that internet utilization is quite influential among students at Bina Agung Medan Junior High School.